Cast imitation Roman imperial denarii finds in Podillya region - Boiko-Haharin, Andrii; Sustrietov, Anatolii; Zadorozhnia, Alina (Acta Archaeologica Lodziensia, 2022)
The study of the influence of the Roman Empire on the tribes of Chernyakhiv culture still remains controversial in many aspects. One of the mysterious questions is the existence in Podillya region of the cast copies made by the locals, of Roman denarii minted in I-III centuries AD. Archaeologists have discovered the remains of foundries in different parts of Podillya which have allowed the location of the centers of these coins production. But the question of the period of their production, their exact function in the life of the population, and the chronology of their circulation still remains uncertain. Gathering new evidence about finds of cast copies of Roman denarii in Podillya, we found a high concentration of finds in the Krasylivsky district of the Khmelnytsky region. This allows us to suggest the presence in this area of another potential center for their manufacture, which can be confirmed by the discovery of the remains of a foundry. The chemical composition of the cast copies of Roman denarii from Podillya tends more towards bronze with a predominance of copper or tin in the alloy. Publishing information about a new finds of cast copies of Roman denarii, and further localization of their sites, will help us to understand the relationship between the Roman Empire and the «Barbaric» world better, thus opening a new page in the cultural relationship between our lands with Rome.